La classe e lo stile: i votivi a impasto rosso-bruno dal santuario di Diana a Nemi - Diosono, Francesca; Giannino, Isabella; Ferrari, Chiara Giulia; Borgers, Barbara (O T I V M, 2024)
The paper examines the as-yet unpublished fictile votive offerings made of impasto rosso-bruno which emerged during the 2009-2021 excavations at the Sanctuary of Diana at Lake Nemi (Rome). Although these finds quantitatively represent a minority compared to the overall votive material, the use of this particular ceramic class, typical of Southern Etruria and Latium Vetus between the late 7th and the 5th century BC, allows us to consider them, with relative certainty, as the oldest ritual offerings present within the sanctuary. The iconographic analysis of these materials highlights a discrepancy between their stylistic dating, traditionally attributed to impasto rosso-bruno as a ceramic class, but thin-section analysis has confirmed that votives and ceramics in impasto rosso-bruno in Nemi were produced using the same technology, and possibly in the same workshops.